Cutaneous B‐lymphoblastic lymphoma with IL3/IgH translocation presenting with hypereosinophilia and acute endocarditis. Issue 6 (8th November 2014) - Bomken, Simon; Haigh, Shaun; Bown, Nick; Carey, Peter; Wood, Katrina; Windebank, Kevin
<x xml:space="preserve">Abstract</x> Hypereosinophilia is a rare phenomenon associated with childhood malignancy, predominantly acute lymphoblastic leukaemia. Causation is unclear and likely to have multiple mechanisms. We report a six year old boy presenting with hypereosinophilia and associated Loeffler endocarditis. Three months following his initial hypereosinophilia he developed cutaneous B‐lymphoblastic lymphoma. Re‐analysis of apparently uninvolved bone marrow, taken at initial presentation, revealed a single, previously unidentified, t(5;14)(q31;q32) positive cell. Using fluorescent in situ hybridisation, we demonstrate IL3/IgH@ fusion in cutaneous lymphoma cells. Our case confirms the association of hypereosinophilia and B‐lymphoblastic lymphoma and strengthens the association between IL3 hypersecretion and hypereosinophilia. Pediatr Blood Cancer 2015;62:1055–1057. © 2014 Wiley Periodicals, Inc.